Associa????o dos polimorfismos I/D do gene da ECA e R557X do gene da ACTN3 aos indicadores de desempenho em jovens atletas da nata????o brasileira - Albuquerque Neto, Severino Le??o de (2018)
The search for better sports performance has encouraged studies on the interaction between environmental and genetic factors. In this perspective, while environmental factors stimulate morphofunctional adaptations, genetic polymorphisms modulate the genes responsible for these adaptations. Therefore, the identification of the candidate genes and their respective polymorphisms with potential to influence the phenotypes related to this performance have been the target of the researchers of the area. Among the promising polymorphisms are the I/D of the angiotensin converting enzyme (ACE) gene and the ??-actinin-3 (ACTN3) gene R577X. In the field of sports genetics, swimming has been studied, but research on the younger athletes is rare. The objective of this study was to analyze the association between ACE and ACTN3 polymorphisms in sports performance indicators in 120 brazilian swimmers (75 Boys and 45 Girls), aged 15 to 17 years (16.76 ?? 0.6 years ), affiliated to the Brazilian Confederation of Aquatic Sports. 102 non-athletes of the same age group (16.51 ?? 0.95 years) residing in the Federal District were part of the control group (56 Boys and 46 Girls). These were subdivided by official swimming tests (short: ???200m vs long: ???400m), related to the phenotypes of sports performance (strength vs. power) and by the competitive level (elite vs. sub-elite). The elite status (international experiences) and the technical index (TI) were adopted as indicators of performance. It was also evaluated the total genothype score (TGS) associated to the strength / power phenotypes. The technique of scraping buccal mucosa epithelial cells with the aid of a specific swab was used to collect the samples. In the athletes was collected during the XXIV Brazilian Junior Swimming Championship and among the students, in the intervals of the Physical Education classes. The genotyping of the polymorphisms was performed through the polymerase chain reaction technique obeying standardized and scientifically validated protocols. All the volunteers signed the agreement with prior consent of those responsible. Chi-square and Mann-Whitney tests were used when the variables were not normally distributed. Pearson's correlation and t-test for independent samples were used for the parametric data. The groups (athletes and non-athletes) demonstrated Hardy-Weinberg equilibrium for the genotypic and allelic distribution of polymorphisms. Sub-elite athletes (???200m and ??? 400m) presented allelic and genotype frequencies in both polymorphisms very close to those observed for the control group. The elite group of athletes was formed by specialists in short competitions (???200m). Significant primacy of the DD genotype of ACE was observed for elite athletes. The D allele and DD genotype were also predominant among athletes of the same phenotypic (strength/power) group identified in the upper quartile (Q3) of TI, with significant differences especially in favor of elite athletes. Analysis of the ACTN3 polymorphism revealed that the R allele was predominant in all groups, except for the elite group, which had a frequency of the heterozygote RX genotype significantly higher. The best TI???s were verified among the athletes (???200m) genotyped for RX and RR, with supremacy for the homozygote among elite athletes. In the joint evaluation of the two polymorphisms, the elite group presented significant genotypic supremacy of DD + RX addition compared to the other groups that presented higher occurrence of DD + RR homozygotes. The TGS analysis showed that athletes with better genotype profiles (score ???75) also had the best TI???s. The results of the study suggest that the elite status and the best TI???s verified among juvenile athletes were influenced positively by the genotype associations typically expected.